Epidemiological versus meteorological forecasts: best practice for linking models to policymaking - Bazo Zambrano, Juan Carlos (2021)
Weather forecasts, climate change projections, and epidemiological predictions all represent domains that are using forecast data to take early action for risk management. However, the methods and applications of the modeling efforts in each of these three fields have been developed and applied with little cross-fertilization. This perspective identifies best practices in each domain that can be adopted by the others, which can be used to inform each field separately as well as to facilitate a more effective combined use for the management of compound and evolving risks. In light of increased attention to predictive modeling during theCOVID-19 pandemic,we identify three major areas that all three of these modeling fields should prioritize for future investmentand improvement: (1) decision support, (2) conveying uncertainty, and (3) capturingvulnerability.